Pengaruh Pemberian Beberapa Jenis Pupuk Kandang dan Pupuk Hijau Terhadap Ketersediaan dan Serapan Nitrogen pada Jagung di Tanah Podsolik - Noor Azizah Febriani; Hairil Ifansyah; Ratna Ratna (Acta Solum, 2023)
The study aimed to determine the effect of application fertilizer derived from animals (manure) or plants (green manure) on the supply and absorption of plant N, changes in pH, CEC, and suppressing Al solubility and to determine the best type of organic matter in supplying and absorbing plant N, change in pH, CEC, and suppress Al solubility. This study was carried out in the field and arranged using a single factor completely randomized design (CRD). The treatments applied in study were K0 = control, K1 = cow manure (50 g pot-1), K2 = goat manure (50 g pot-1), K3 = chicken manure (50 g pot-1), K4 = green manure for weed hair buns (50 g pot-1), K5 = rice straw green manure (50 g pot-1), K6 = gamal green fertilizer (50 g pot-1). The application of various organic materials can increase pH, CEC, available N, plant dry weight, N uptake of corn plants, and reduce Al solubility.